EMISSIONS OF ASH SOLID ARTICLES FROM THERMAL РOWER PLANTS WHEN SOLID FUEL IS COMBUSTED - Sheleshey, Tetiana; Bednarska, Inna; Kutsa, Alina; Granishevs’ka, Anzhela; Shumnik, Olena (Sworld-Us Conference proceedings, 2023)
Scientific and technological progress is spreading at a rapid pace. Technologies are gradually being improved, the mechanisms of various apparatuses and devices are being modernized. Working conditions are improving at enterprises that largely depend on t